2022
DOI: 10.1002/slct.202200288
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, In Vitro Cytotoxicity, and DFT Studies of Novel 2‐Amino Substituted Benzonaphthyridines as PDK1 Inhibitors

Abstract: The present work emphasizes the utility of 2,4‐dichloro‐5‐methylbenzo[h][1,6]naphthyridine as starting precursors. The reaction of 2,4‐dichloro‐5‐methylbenzo[h][1,6]naphthyridine with a variety of aliphatic and aromatic amines yielded 2‐amino substituted 2,4‐dichlorobenzo[h]naphthyridines. All the compounds were examined for their in vitro anticancer activity against six human cancer lines and docked with PDK1 inhibitors. The structure‐activity relationship studies are revealed that the compounds holding amino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 53 publications
(92 reference statements)
0
2
0
Order By: Relevance
“…For our studied compounds, stretching frequency of C=N bond is calculated in the range of 1461 -1531 cm -1 [23] As for the other peaks, the stretching frequencies of CO and CN are calculated nearly 1310 and 960 cm -1 , respectively. These frequencies, CO and CN, have been reported in the range of 1334 -1417 and 925 -970, respectively [23,24].…”
Section: Optimized Structuresmentioning
confidence: 80%
“…For our studied compounds, stretching frequency of C=N bond is calculated in the range of 1461 -1531 cm -1 [23] As for the other peaks, the stretching frequencies of CO and CN are calculated nearly 1310 and 960 cm -1 , respectively. These frequencies, CO and CN, have been reported in the range of 1334 -1417 and 925 -970, respectively [23,24].…”
Section: Optimized Structuresmentioning
confidence: 80%
“…The structureactivity relationship revealed that the compounds holding aminocarbazole moiety and triazole amine moiety increased the activity profile. Afterwards, all of them were also evaluated in vitro against six human cancer cell lines (A549, HCT-15, T47D, C6, HepG2, and Hep-2), showing a potent activity [108].…”
Section: Fused Heterocyclic Ringsmentioning
confidence: 99%